Eutrophication model for river-type reservoir tributaries and its applications - Ling-ling Wang; Zhen-zhen Yu; Hui-chao Dai; Qing-hua Cai (Water Science and Engineering, 2009)
With the impoundment of the Three Gorges Reservoir, algal blooms have been found in some tributaries. In this study, according to the theoretical analysis of the eutrophication mechanism in a river-type reservoir tributary, a one-dimensional eutrophication model was developed for the Xiangxi River tributary of the Three Gorges Reservoir, and the influence of hydrodynamic conditions on the primary growth rate of algae was investigated. Furthermore, numerical predictions of hydraulic variables and eutrophication factors, such as the concentration distribution of TP, TN, and Chl-a in the spatial and temporal domains, were carried out. Comparison of computation results of TP, TN, and Chl-a concentrations along the river in the spring of 2005 with experimental data demonstrates the validity of the model. The agreement between the computation results and the experimental data of TP and TN concentrations is better than the agreement between those of Chl-a concentration. The simulated results also show that the Chl-a concentration downstream is much higher than that in the upstream tributary, which potentially indicates the outbreak of algae in this area. Therefore, this study provides a feasible method of accurately predicting the state of eutrophication in river-type reservoirs and their tributaries.